PENGARUH KUALITAS PELAYANAN PERPAJAKAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA MEDAN BELAWAN - Lubis, Reza Hanafi (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2017)
The objective of this research is to measure the influence of tax service quality and tax sanctions to taxpayer compliance in Tax Service office (KPP) Pratama Medan Belawan. This research using survey method for approachment. The nature and type of this research are to explain and quantitative descriptive. The sample of this research are 100 tax payer in KPP Pratama Medan Belawan using simple random sampling. This research was using questionnaire for data collection method. The questionnaire was given to any tax payer randomly. The result of this research which has passed through validity test, reliability test and classic assumption test were processed and resulting the following regression equation, Y = 0.351 X1 + 0.343 X2 + e. The result of multiple regression shows that tax service quality and tax sanctions has a postive influence to taxpayer compliance in KPP Pratama Medan Belawan. The value of determination coefficient (RÂ²) was 0.579. It means 57.9% taxpayer were affected by tax service quality and tax sanctions, 40.1% taxpayer compliance can be were affected by the variable outside the two variable.Keywords: Tax service quality, tax sanction, taxpayer compliance